85.7k views
1 vote
Solve for x

-3(-3x-1) +2x+2=27​

2 Answers

5 votes

Answer:


x=2

Explanation:

So we have the equation:


-3(-3x-1)+2x+2=27

First, distribute the -3:


9x+3+2x+2=27

Combine like terms:


11x+5=27

Subtract 5 from both sides:


11x=22

Divide both sides by 11:


x=2

So, the value of x is 2.

And we're done!

User Elledienne
by
5.0k points
3 votes

Steps to solve:

-3(-3x - 1) + 2x + 2 = 27

~Distribute

9x + 3 + 2x + 2 = 27

~Combine like terms

11x + 5 = 27

~Subtract 5 to both sides

11x = 22

~Divide 11 to both sides

x = 2

Best of Luck!

User AaronMK
by
5.1k points